Factors Influencing Enterprise Resource Planning System: A Review - Hasan, M.S.; Ebrahim, Z.; Mahmood, W.H.W.; Rahman, M.N.A (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The purpose of this paper is to provide a comprehensive review on factors that influence the enterprise resource planning system (ERP-S) implementation from literature studies between 2011 and 2016. A set of criteria was set to explore ERP-S related research articles through academic search engines and academic databases. Selected articles were categorized into critical success failure factors (CSFF), ERP-S user factors, and ERP-S assimilation factors. The findings from this paper provides a deeper understanding to both academicians and industrial practitioners regarding ERP-S success factors. A strategic plan can also be developed to ensure successful ERP-S implementation.